2022
DOI: 10.18502/jovr.v17i1.10168
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of the PalmScan VF2000 Virtual Reality Visual Field Analyzer for Identification and Classification of Glaucoma

Abstract: Purpose: To evaluate the diagnostic test properties of the Palm Scan VF2000® Virtual Reality Visual Field Analyzer for diagnosis and classification of the severity of glaucoma. Methods: This study was a prospective cross-sectional analysis of 166 eyes from 97 participants. All of them were examined by the Humphrey® Field Analyzer (used as the gold standard) and the Palm Scan VF 2000® Virtual Reality Visual Field Analyzer on the same day by the same examiner. We estimated the kappa statistic (including 95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Several studies have examined VR‐based perimeters. For example, Shetty et al 12 and Mees et al 13 showed that VR platforms may be useful when screening for glaucomatous visual field defects using the criteria of number of defective points identified. Other studies using different thresholding paradigms, such as that by Narang et al, 14 Razeghinejad et al 15 and Tsapakis et al 16 against the HFA and Stapelfeldt et al 17 against the Octopus, showed results that correlated well with standard automated perimetry.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined VR‐based perimeters. For example, Shetty et al 12 and Mees et al 13 showed that VR platforms may be useful when screening for glaucomatous visual field defects using the criteria of number of defective points identified. Other studies using different thresholding paradigms, such as that by Narang et al, 14 Razeghinejad et al 15 and Tsapakis et al 16 against the HFA and Stapelfeldt et al 17 against the Octopus, showed results that correlated well with standard automated perimetry.…”
Section: Introductionmentioning
confidence: 99%